Efficient in vitro and in vivo pulmonary delivery of nucleic acid by carbon dot-based nanocarriers. (May 2015) - Pierrat, Philippe; Wang, Rongrong; Kereselidze, Dimitri; Lux, Marie; Didier, Pascal; Kichler, Antoine; Pons, Françoise; Lebeau, Luc
Abstract: Cationic carbon dots were fabricated by pyrolysis of citric acid and bPEI25k under microwave radiation. Various nanoparticles were produced in a 20–30% yield through straightforward modifications of the reaction parameters (stoichiometry of the reactants and energy supply regime). Particular attention was paid to the purification of the reaction products to ensure satisfactory elimination of the residual starting polyamine. Intrinsic properties of the particles (size, surface charge, photoluminescence and quantum yield) were measured and their ability to form stable complexes with nucleic acid was determined. Their potential to deliver plasmid DNA or small interfering RNA to various cell lines was investigated and compared to that of bPEI25k. The pDNA in vitro transfection efficiency of these carbon dots was similar to that of the parent PEI, as was their cytotoxicity. The higher cytotoxicity of bPEI25k/siRNA complexes when compared to that of the CD/siRNA complexes however had marked consequences on the gene silencing efficiency of the two carriers. These results are not fully consistent with those in some earlier reports on similar nanoparticles, revealing that toxicity of the carbon dots strongly depends on their protocol of fabrication. Finally, these carriers were evaluated for in vivo gene delivery through the non-invasive pulmonary route in mice. High transgene expression was obtained in the lung that was similar to that obtained with the golden standard formulation GL67A, but was associated with significantly lower toxicity. Post-functionalization of these carbon dots with PEG or targeting moieties should significantly broaden their scope and practical implications in improving their in vivo transfection efficiency and biocompatibility.